2009
DOI: 10.1111/j.1467-9701.2009.01183.x
|View full text |Cite
|
Sign up to set email alerts
|

Trade Liberalisation and Poverty Reduction in Vietnam

Abstract: This paper investigates the impacts of trade liberalisation on poverty reduction in Vietnam during the period of economic reform. Using a combined approach dealing with four transmitting channels from trade to poverty, the major findings are summarised as follows. First, Vietnam's trade liberalisation has fostered economic growth, which has helped to raise per capita GDP and reduce poverty. Second, trade liberalisation has directly benefited the poor through creating pro-poor employment and raising wages. Thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…i Critics highlight the relatively high concentration of poor households near the poverty line during the 1990s as a likely explanation for the pro-poor nature of growth in Vietnam. They also highlight the persistence of a high poverty gap in rural areas, in the Northern Mountain and the inland Central Highland regions as well as increased inequality throughout the country, resulting in an extensive urban-rural division, with the richest 20 per cent of the population living in urban areas (Heo and Doanh, 2009). Furthermore, trade openness seems to have promoted a distributional impact within the rice sector too, further penalizing the poorer small net producers (Coello et al, 2010).…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…i Critics highlight the relatively high concentration of poor households near the poverty line during the 1990s as a likely explanation for the pro-poor nature of growth in Vietnam. They also highlight the persistence of a high poverty gap in rural areas, in the Northern Mountain and the inland Central Highland regions as well as increased inequality throughout the country, resulting in an extensive urban-rural division, with the richest 20 per cent of the population living in urban areas (Heo and Doanh, 2009). Furthermore, trade openness seems to have promoted a distributional impact within the rice sector too, further penalizing the poorer small net producers (Coello et al, 2010).…”
Section: Notesmentioning
confidence: 99%
“…Over the first ten years after the adoption of the "Doi Moi" (renovation), a combination of stabilization, liberalisation and structural reforms, the annual average growth rate of Vietnam's merchandise exports boomed at 25 per cent (1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996), and it fell only to 18.5 per cent in the subsequent decade (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006). An extensive empirical literature highlights the importance of this trade surge on the Vietnamese economy, identifying the positive correlations between trade liberalisation, growth and poverty reduction (Irvin, 1997;Fritzen, 2002;Jenkins, 2004;Nadvi et al, 2004;van de Walle & Cratty, 2004;Jensen & Tarp, 2005;Nguyen & Ezaki, 2005;Fujii & Roland-Holst, 2008;Niimi et al, 2007;Abbott et al, 2009 ;Heo & Doanh, 2009;Coello et al, 2010;Hoang et al, 2016). i The growth of average income is obviously hugely important to economic welfare, but even for an individual household it is not the only thing that matters.…”
Section: Introductionmentioning
confidence: 99%
“…In China, much of the export products originated from rural areas right after the opening‐up policy in late 1970s, and later shifted to special economic zones, coastal regions and the rest of the country, which has benefited vast number of off‐farm employment of rural farmers and contributed to rural poverty reduction. The literature has also showed that trade liberalization has contributed to the reduction of poverty in Vietnam (Heo and Doanh, 2009), India (Bhagwati and Srinivasan, 2002), and the Philippines (Cororaton and John, 2007).…”
Section: Drivers Of Inclusive Rural Transformationmentioning
confidence: 99%
“…T rade liberalization and export orientation of the economy have intensified rice production tremendously in Vietnam during the last decades. Rice has become a top export of the country (Heo and Doanh, 2009). In 2008, about 44% of the total farmed area was thus under paddy rice cultivation; the total rice production of Vietnam was 38.7 Mt (GSO, 2010).…”
Section: Selected Studies On Pesticide Behavior In Paddy Water and Pementioning
confidence: 99%